Vitamin D promotes human extravillous trophoblast invasion in vitro. Issue 4 (April 2015) - Chan, S.Y.; Susarla, R.; Canovas, D.; Vasilopoulou, E.; Ohizua, O.; McCabe, C.J.; Hewison, M.; Kilby, M.D.
Abstract Introduction Incomplete human extravillous trophoblast (EVT) invasion of the decidua and maternal spiral arteries is characteristic of pre-eclampsia, a condition linked to low maternal vitamin D status. It is hypothesized that dysregulated vitamin D action in uteroplacental tissues disrupts EVT invasion leading to malplacentation. Methods This study assessed the effects of the active vitamin D metabolite, 1, 25-dihydroxyvitamin D3 (1, 25-D3), and its precursor, 25-hydroxyvitamin D3 (25-D3), on primary human EVT isolated from first trimester pregnancies. Expression of EVT markers (cytokeratin-7, HLA-G), the vitamin D-activating enzyme (CYP27B1) and 1, 25-D3 receptor (VDR) was assessed by immunocytochemistry. EVT responses following in vitro treatment with 1, 25-D3 (0–10 nM) or 25-D3 (0–100 nM) for 48–60 h were assessed using quantitative RT-PCR (qRT-PCR) analysis of key target genes. Effects on EVT invasion through Matrigel® were quantified alongside zymographic analysis of secreted matrix metalloproteinases (MMPs). Effects on cell viability were assessed by measurement of MTT. Results EVT co-expressed mRNA and protein for CYP27B1 and VDR, and demonstrated induction of mRNA encoding vitamin D-responsive genes, 24-hydroxylase (CYP24A1) and cathelicidin following 1, 25-D3 treatment. EVT could respond to 1, 25-D3 and 25-D3, both of which significantly increased EVT invasion, with maximal effect at 1 nM 1, 25-D3 (1.9-fold; p < 0.01) and 100 nM 25-D3 (2.2-fold; p < 0.05) respectively compared with untreated controls. This was accompanied by increased pro-MMP2 and pro-MMP9 secretion. The invasion was independent of cell viability, which remained unchanged. Discussion These data support a role for vitamin D in EVT invasion during human placentation and suggest that vitamin D-deficiency may contribute to impaired EVT invasion and pre-eclampsia.